Analisis Pengelompokan Heterogen Usia Berdasarkan Kemampuan Membaca Al-Quran TPA Darussalam - Ainurrochma Triyanti; Imelda Dwi A; Salma Azzahra; Heriyanto Susilo; Desika Putri Mardiani (LP3M STAI MA'ARIF MAGETAN, 2025)
Education is the right of every individual that can be obtained through formal, informal and non formal education. One of them is non formal education in the form of Al-Qur'an education parks, TPA has an important role in building character and spiritual values, especially in children in the developmental period. TPA Darussalam, which was established in Mulyorejo Baru, developed a learning system based on grouping the ability to read the Qur'an, with an active and sustainable learning approach. This study aims to analyze age grouping based on the ability to read the Qur'an on children's spiritual competence and values. Using a qualitative approach, data were collected through interviews, observation, and documentation. The results showed that grouping based on ability can create cross-age interactions that can increase competence, motivation and responsibility in children. Forming Islamic character and strengthening spiritual values. However, there are problems in the form of dependence between students and potential conflicts that have a major effect on the effectiveness of the teaching and learning process.